Synthesis of Zeolite from Bagasse and Rice Husk Ashes as Surfactant Builder on Detergency Process: Variation of NaOH Concentration for Silica Isolation - Arnelli Arnelli; Bara Yunianto Fathoni; Teguh Iman Prastyo; Ahmad Suseno; Yayuk Astuti (Jurnal Kimia Sains dan Aplikasi, 2018)
Zeolite was successfully synthesised from ash bagasse and from rice husk ash as source of silica and applied to surfactant builder. The removal of silica from bagasse ash and from rice husk ash was influenced by NaOH concentration to obtain sodium silicate. This research aimed to synthesize zeolite, determine the optimum concentration of NaOH to synthetic zeolite, identify the zeolite mineral type, morphology, determine cation exchange rate and detergency by using synthesized zeolite as builder. Synthesis of zeolite was undertaken by sol-gel method followed by hydrothermal process. The stages of this study included the production of bagasse and rice husk ashes, isolation of silicate using a variation of NaOH concentration of 1.67, 3.33, 5.00, 6.67 and 8.30 M in the form of sodium silicate. Synthesis of zeolite was carried out by reacting sodium silicate and sodium aluminate using hydrothermal method. The synthesized zeolites were characterized using XRD and SEM. The results of this research indicated the types of zeolite minerals formed, namely, zeolite A, Na-A, Na-Y and sodalite. The morphology of the synthesized zeolites from both samples was quite homogeneous, NaOH concentration used to produce zeolite from bagasse ash was 1.67 M with value of cation exchange capacity (CEC) and detergency were respectively 121.14 mek/100 gram and 92.09% while synthesis zeolite from rice husk ash was generated using 8.3 M NaOH concentration with value of cation exchange capacity (CEC) and detergency were 65,71 mek / 100 gram and 94,313%, respectively.